2012
DOI: 10.1002/adsc.201200164
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Tandem Synthesis of 2‐Arylbenzoxazole Derivatives via Copper‐Catalyzed CN and CO Bond Formation

Abstract: The reaction of 2-(2-halophenyl)halobenz-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…[5] Very recently, Ma and co-workers reported on the synthesis of dibenzodiazepinone from 2-bromo-N- (2-bromophenyl)benz-A C H T U N G T R E N N U N G amide and various primary amines using a Cu(I) catalyst. [6] However, in our recent publication, we found that the product formed is, in fact, the N-substituted-2-(benzo [d]oxazol-2-yl) (B), as confirmed by 1 H NMR, 13 C NMR, LRMS, HR-MS and single crystal X-ray analysis data (Scheme 1) [7] and is not the dibenzodiazepinone derivative (A). Thus, an efficient, one-pot protocol for the synthesis of dibenzodiazepinone derivatives continues to be highly desirable.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…[5] Very recently, Ma and co-workers reported on the synthesis of dibenzodiazepinone from 2-bromo-N- (2-bromophenyl)benz-A C H T U N G T R E N N U N G amide and various primary amines using a Cu(I) catalyst. [6] However, in our recent publication, we found that the product formed is, in fact, the N-substituted-2-(benzo [d]oxazol-2-yl) (B), as confirmed by 1 H NMR, 13 C NMR, LRMS, HR-MS and single crystal X-ray analysis data (Scheme 1) [7] and is not the dibenzodiazepinone derivative (A). Thus, an efficient, one-pot protocol for the synthesis of dibenzodiazepinone derivatives continues to be highly desirable.…”
Section: Introductionmentioning
confidence: 71%
“…Further, the amides derived from 2-iodobenzoic acid and ortho-substituted anilines reacted smoothly with 2-iodoanilines (2a and 2c) to furnish the corresponding dibenzodiazepinone derivatives in moderate to good yields. It is worth noting that the 2-halo-N-phenylbenzamides derived from electron-withdrawing ortho-substituted anilines such as F, Cl, NO 2 required a longer reaction time than for those with electron-donating groups (entries [3][4][5][6][7][8][9]. Moreover, 2-iodobenzamides derived from m-methoxyaniline and p-isopropylaniline produce compounds 5q and 5r in moderate yields (entries 10 and 11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the recent times, copper‐catalyzed tandem sequential cyclization reactions of 2‐halobenzamide derivatives have proven to be powerful tools for the construction of a wide variety of heterocyclic frameworks 7. In our recent research, we focused our attention on copper‐catalyzed CC and CN bond formation reactions of 2‐iodobenzamide derivatives in the construction of various heterocycles, including indoloquinolinone derivatives,8a 2‐aminophenylbenzoxazoles8b and isocoumarin derivatives 8c. On the other hand, it was reported that benzyl cyanide works as a nucleophile in the presence of strong bases 9.…”
Section: Introductionmentioning
confidence: 99%